The Role of Coping Strategies and Social Competence in Predicting the Social Skills of Single-Child University Students - Fani Mohammadabady , Maryam; Namvar, Hooman; Atashpour, Seyed Hamid (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2025)
Objective: The present study aimed to investigate the role of coping strategies and social competence in predicting the social skills of single-child university students in Isfahan.Methods and Materials: This study is categorized as fundamental research and was conducted within the framework of a correlational design using the structural equation modeling (SEM) approach. The statistical population comprised all 18- to 22-year-old university students born into single-child families in Isfahan in 2024, estimated at approximately 520 individuals. To enhance the generalizability of the findings, a total of 250 single-child students were selected for participation. Data were collected using the Social Skills Questionnaire by Inderbitzen and Foster (1992), the Coping with Stressful Situations—Short Form by Kallasbeek et al. (1990), the Revised Differentiation of Self Inventory by Skowron and Schmitt (2003), the Schneider et al. (1991) Questionnaire, the Social Competence Questionnaire by Behini (2007), and the Attitudes and Beliefs Scale by David et al. (2019). Statistical analysis of the data revealed that, in the fitted model, the direct effect of beliefs on social skills was significant at the 0.01 level.Findings: The direct effect of the avoidant coping style on social skills was not significant. The direct effect of the emotion-focused coping style on social skills was significant at the 0.05 level. The direct effect of differentiation of self on hope was significant at the 0.01 level. The direct effect of the problem-focused coping style on hope was significant at the 0.01 level. The direct effect of the emotion-focused coping style on hope was also significant at the 0.01 level. The direct effect of social competence on social skills was significant at the 0.01 level. Additionally, the direct effect of hope on social skills was significant at the 0.01 level.Conclusion: Based on these findings, it can be concluded that all first-level variables in the model (i.e., differentiation of self, beliefs, and coping styles) had a significant indirect effect on social skills through the mediating roles of social competence and hope. In other words, social competence and hope played an effective mediating role in the relationship between these variables and social skills.